Theoretical aspects of computing--ICTAC 2011 8th international colloquium, Johannesburg, South Africa, August 31-September 2, 2011 : proceedings - Cerone, Antonio; Pihlajasaari, Pekka (Lecture Notes in Computer Science, 2011)
Thiis book constitutes the refereed proceedings of the 8th International Colloquium on Theoretical Aspects of Computing, ICTAC 2011 held in Johannesburg, South Africa, in August/September 2011. The 14 revised full papers presented together with the abstracts of three keynote talks were carefully reviewed and selected from 44 submissions. The papers address various theoretical aspects and methodological issues of computing and are organized in topical sections on grammars, semantics, modelling, the special track on formal aspects of software testing and grand challenge in verified software, on logics, as well as algorithms and types.